Digital Marketing Strategy for Fashion Products on Tiktok (Syntax Corporation Indonesia, 2025)
This research discusses the continuously evolving digital era, where marketing strategies play a crucial role in achieving sustainable sales growth in the e-commerce sector. The study aims to explore digital marketing strategies for fashion products on the TikTok platform, with an emphasis on efforts to connect consumers and businesses through social media. The applied research method is qualitative, allowing the researcher to gain deeper insights into the marketing practices being implemented. The analysis of the digital marketing strategies employed by account @akun @baldovino.co reveals that increased customer engagement is achieved through a combination of organic and paid methods. The use of TikTok's data analytics features, active interaction in the comment section, keyword optimization in content, and the implementation of TikTok Ads have proven effective in enhancing brand visibility and awareness. This research is also supported by the digital marketing theory developed by Chakti, 2022.